(untitled) - Wohlfahrtswerk für Baden-Württemberg, Ingrid Hastedt, Vorsitzende des Vorstandes (Blätter der Wohlfahrtspflege (BdW), 2023)
Blätter der Wohlfahrtspflege informs about vital social and legal developments as well as standards in health and social services. It contains essential articles, model descriptions, and provides useful aids. It offers extensive information on orientation in all fields of social work as well as social services and facilities. The journal addresses all professionals in the social services – social workers, social education workers, educators, scholars, head officials, executives, and chairmen of organizations. Website: www.bdw.nomos.de